To find the derivative of y with respect to x, we can use the chain rule. Let's denote u = 2x - √(x), then y = csc(u).
The derivative of y with respect to x, dy/dx, can be found as:
dy/dx = dy/du * du/dx
We know that du/dx = 2 - 1/(2√(x)).
To find dy/du, we can rewrite y = csc(u) as y = (1/sin(u)), and then find its derivative with respect to u:
(dy/du) = d(1/sin(u)) / du
Applying the chain rule, we have:
(dy/du) = -1/(sin^2(u)) * (du/du)
(dy/du) = -1/(sin^2(u))
Now, we can substitute du/dx and dy/du back into the chain rule equation:
dy/dx = dy/du * du/dx
= (-1/(sin^2(u))) * (2 - 1/(2√(x)))
Substituting back u = 2x - √(x):
dy/dx = (-1/(sin^2(2x - √(x)))) * (2 - 1/(2√(x)))
Therefore, dy/dx = (-1/(sin^2(2x - √(x)))) * (2 - 1/(2√(x)))
Find dydx if y=csc(2x−−√) .
1 answer